Bank switching behaviour of local graduates in Singapore - Lim, Susan (2008)
The research sought to establish the extent to which local graduates aged 22 to 36 had switched their main/sole bank since graduating and the reasons which led to their decision to switch banks. The research also attempted to distinguish graduate switchers from non-switchers, using a range of demographics and psychographics characteristics.